Nurses’ Knowledge And Skills About Of Caring Of Patients’ Schizophrenia At Jeddah General Hospitals (The Review of Diabetic Studies, 2025)
Background Schizophrenia is a psychological condition that is lifelong in nature and advanced nursing is essential. Nurses are in a significant position to guarantee the best patient outcomes in the psychologically schizophrenia patients with effective appraisal and administration and psychosocial services. Nonetheless, quality care provision may be hindered by knowledge and skills gaps in nurses who cannot deliver quality care due to insufficient specific training in some general hospitals.Aim: The research was aimed at evaluating both clinical skills and the degree of knowledge of nurses in general hospitals in Jeddah in relation to providing care to schizophrenic patients.Method: It was performed in a quasi-Experimental research design. The study sample consisted of a group of 100 nurses employed at Jeddah general hospitals in reference to a validated instrument that gauged the level of knowledge and competency in relation to caring about schizophrenia. Descriptive statistics were used in analyzing the data to determine the level of competency.Results: According to results, it was determined that 35 percent of nurses had a below 50 scores which meant a low level of knowledge and skills. Half of its scores ranged between 51-70 which indicates that they are fairly competent, whereas only 14 per cent showed very good knowledge and competence with scores of between 71-90. Only 1% demonstrated high levels of competency (above 91) indicating that there is a very large gap in knowledge and skill level between nurses in general hospitals in providing care to patients with schizophrenia.Conclusion: The research highlights the necessity of specific educational activities and in-service training to increase the competencies of nurses to treat patients diagnosed with schizophrenia. Development of these competencies can play a crucial role in enhancing patient well-being, decreasing the rates of relapse and providing comprehensive psychiatric help.